Decision management - reddy, Harinath (Journal of Management and Science, 2020)
The phrase decision management can also be expressed as being an enterprise decision management or EDM or that of BDM or business decision management.This will be encompassing any aspects in relation to that of management, building and designing of systems which take decisions in an automated way. These are often used by organisations to be managing the kind of interactions they have with their suppliers, employees and customers. Computing or computerisation has been changing the ways in which organisations are bound to be making decisions. More and more decisions are being made in an automated way.